The Influence Of Third-Party Funds, Capital Adequacy Ratio, And Bi Rate On Bank Lending In Indonesia - Sabaruddin Siagian; Faizal Roni (Jurnal Ilmiah Multidisiplin, 2025)
This study investigates the impact of third-party funds, capital adequacy ratio, and BI rate on bank lending performance in Indonesia in the post-pandemic period. Utilizing a quantitative approach and secondary data from official financial institutions, the research applies multiple linear regression analysis along with classical assumption tests to ensure statistical validity. The results indicate that third-party funds do not have a significant effect on bank lending. On the other hand, the capital adequacy ratio shows a strong positive and significant influence, reflecting the crucial role of bank capitalization in credit expansion. Meanwhile, the BI rate does not present a statistically significant impact on credit distribution. However, when the three variables are tested simultaneously, they collectively exert a positive and significant influence on bank lending. These findings provide meaningful insights for banking institutions and regulators to develop sound credit policies and financial strategies that support economic recovery and sustainable banking practices.